INTERVIEW WITH SOCIOLINGUIST JUAN MANUEL HERNANDEZ-CAMPOY - Almeida Sandes, Egisvanda Isys de [UNESP]; Manjon-Cabeza Cruz, Antonio; Molina Ortes, Elena Fernandez de (Unesp-faculdade Ciencias & Letras, 2020)
This is the interview that Sandes, Manjon-Cabeza Cruz and Molina Ortes do with the important Anglo-Saxon sociolinguist, Juan Manuel Hernandez-Campoy. His research includes sociolinguistics, dialectology and history of the English language, especially on linguistic change and variation, areas in which he has a wide range of publications. In the interview, Hernandez-Campoy discusses several aspects, such as his beginning as a researcher, his investigative line, issues related to the areas with which he works, including exchanges with other English-speaking researchers, controversies and coincidences in discussions between authors, as well as about the importance of sociolinguistics for language teaching.
Keywords: Juan Manuel Hernandez-Campoy. Interview. Sociolinguistics and language teaching